Effect of Addition Elephant Grass Cellulose and CaCO3 Oyster Shell Waste as Bioplastic Composites - M Prayogie Aulia; Reza Rizki; Sri Aprilia; Farid Mulana (Universitas Jenderal Soedirman, 2022)
The effect of adding cellulose and CaCO3 as a bioplastic filler was studied. The source of cellulose is obtained from elephant grass plants, while CaCO3 is obtained from oyster shell waste. The primary raw material for bioplastics is tapioca starch with glycerol as a plasticizer using the solution casting method. The resulting bioplastics are thin and transparent but not very elastic, with a thickness is 1 mm. The mechanical properties test of bioplastics obtained tensile strength between 1-3 MPa and elongation between 1-4.4%. Physical properties test results obtained density between 0.313-0.33 g/mL and water absorption between 31.94-81.16%. The morphological test showed that the bioplastic surface was getting more uneven with more CaCO3 filler. The use of cellulose fillers without the combination obtained better results than cellulose and CaCO3 fillers.